Improved measurement of disease progression in people living with early Parkinson’s disease using digital health technologies - Matthew D. Czech; Darryl Badley; Liuqing Yang; Jie Shen; Michelle Crouthamel; Tairmae Kangarloo; E. Ray Dorsey; Jamie L. Adams; Josh D. Cosman (Communications Medicine, 2024)
Abstract Background Digital health technologies show promise for improving the measurement of Parkinson’s disease in clinical research and trials. However, it is not clear whether digital measures demonstrate enhanced sensitivity to disease progression compared to traditional measurement approaches. Methods To this end, we develop a wearable sensor-based digital algorithm for deriving features of upper and lower-body bradykinesia and evaluate the sensitivity of digital measures to 1-year longitudinal progression using data from the WATCH-PD study, a multicenter, observational digital assessment study in participants with early, untreated Parkinson’s disease. In total, 82 early, untreated Parkinson’s disease participants and 50 age-matched controls were recruited and took part in a variety of motor tasks over the course of a 12-month period while wearing body-worn inertial sensors. We establish clinical validity of sensor-based digital measures by investigating convergent validity with appropriate clinical constructs, known groups validity by distinguishing patients from healthy volunteers, and test-retest reliability by comparing measurements between visits. Results We demonstrate clinical validity of the digital measures, and importantly, superior sensitivity of digital measures for distinguishing 1-year longitudinal change in early-stage PD relative to corresponding clinical constructs. Conclusions Our results demonstrate the potential of digital health technologies to enhance sensitivity to disease progression relative to existing measurement standards and may constitute the basis for use as drug development tools in clinical research.